Development of a Management System for Short Online Learning Courses - Antonio Sarasa-Cabezuelo (MDPI AG, 2021)
In all areas of knowledge, there is a set of basic concepts or ideas that are essential to understand. A very common problem that arises among students is the difficulty in acquiring these concepts. One way to solve this problem is by carrying out small knowledge tests where these concepts are put into practice. To develop these tests there are multiple options, however, in general, the applications that allow for these tests to be implemented are usually very complex and are often included within other larger systems. This article describes a tool to develop short online courses that presents an interface and a functionality that allows a teacher to create and manage courses in a very simple and intuitive way. In the same way, it offers the student an Android app to be able to access the courses published by the teacher to be able to take them, as well as to manage all the activity of it.